(untitled) (Journal of Civil Engineering Researchers, 2021)
Lateral load-bearing systems are part of a structure that has the task of withstanding lateral loads and directing them from a safe path to the foundation. Ancillary forces can include earthquake load, wind load, or other forces. Nowadays, with the increasing use of concrete structures in construction projects, also the basic need to strengthen concrete structures for various reasons such as changing the use of the building, the age of the building and other things, knowing and using new and appropriate methods for Increasing the bearing capacity of concrete building frames against lateral forces is essential and unavoidable. In this article, by reviewing new articles and researches in the field of new types of lateral load reinforcement systems in reinforced concrete frames, the efficiency and productivity of each method have been evaluated and measured.